Lying Aversion and the Size of the Lie - Gneezy, Uri; Kajackaite, Agne; Sobel, Joel (American Economic Review, 2018)
This paper studies lying. An agent randomly picks a number from a known distribution. She can then report any number and receive a monetary payoff based only on her report. The paper presents a model of lying costs that generates hypotheses regarding behavior. In an experiment, we find that the highest fraction of lies is from reporting the maximal outcome, but some participants do not make the maximal lie. More participants lie partially when the experimenter cannot observe their outcomes than when the experimenter can verify the observed outcome. Partial lying increases when the prior probability of the highest outcome decreases. (JEL C91, D12, D90, Z13)